2018
DOI: 10.7577/pp.2381
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Professionalism: Social Workers Negotiating Tools of NPM

Abstract: This article examines how social workers and managers perceive meaningful work and expertise in six care and treatment facilities in Denmark. Based on 29 interviews with social workers (n=22) and managers (n=7), the article shows how New Public Management-inspired tools such as scoring schemas align with social work values such as “client-centeredness” and working with the individual welfare recipient face-to-face. The article finds that fitting social work into organizational schemas changes the work practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 41 publications
0
14
0
3
Order By: Relevance
“…11,[14][15][16] Within the literature on professions and organizations, there is a rich body of micro-level studies concerned with working across sectors, organizations and professions. [17][18][19][20][21] However, such studies focus on individual professionals and fail to acknowledge the specific resources of professions as collective actors. Studies analyse individual professions and their particular roles in integrated care.…”
Section: Introductionmentioning
confidence: 99%
“…11,[14][15][16] Within the literature on professions and organizations, there is a rich body of micro-level studies concerned with working across sectors, organizations and professions. [17][18][19][20][21] However, such studies focus on individual professionals and fail to acknowledge the specific resources of professions as collective actors. Studies analyse individual professions and their particular roles in integrated care.…”
Section: Introductionmentioning
confidence: 99%
“…According to Van Berkel and Knies (2016), there is a risk that values and factors that are highly valuable to the organization are not measured, such as qualitative aspects ( Van Berkel and Knies 2016). When what professionals define as satisfactory results loses importance and the focus is too much on indicators, numbers, and costs, there is a risk that measurements will control the social services to a greater extent than the actual needs of welfare recipients (Lindgren 2014;Mik-Meyer 2018). The introduction of NPM into social work has clearly led to social work being mixed with economic and more industrial premises.…”
Section: Introductionmentioning
confidence: 99%
“…An interview study by Mik-Meyer (2018), in which interviews were conducted with 29 social workers and managers, revealed that social workers are expected to simultaneously balance between working for the client and being co-responsible for the organization's efficiency and results. The findings further revealed that social work today requires a certain amount of documentation while, at the same time, it involves relational work with the welfare recipients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations